The development of interactive learning: mathematics in English for Standard 1 / Sara Sukati - Sukati, Sara (2005)
Multimedia application nowadays is rapidly adapt into every aspects of life. In learning, suggestions in bringing the multimedia and internet into classroom are always being talk about. When it is executed a lot of application needed to be use as for not to waste effort bringing the computer into the classroom. This project will fulfil a little from the need and the development of the similar project will grow in no time. The project developed is for mathematic subject for standard I student. It covers topic numbers until 100, addition and subtraction within 20. The topics covered are following the mathematic syllabus for standard 1. The multimedia elements included in the project are texts, animated texts, sound and graphics or images. The main medium language is English as now the mathematic and science is taught in English for standard 1 and standard 2 classes. The project is hoped to be benefit for the students in their learning.